A Tb-MOF anion, porous coordination framework constructed with oxalate ligand: Crystal structure, adsorption properties, and luminescence sensing. (November 2021) - Cui, Ruifang; Li, Rui; Li, Zheng; Wei, Mingming; Wang, Xiong; Li, Xia
Abstract: The reaction of Tb(NO)3 · 6H2 O and potassium oxalate (ox) yielded the coordination framework, [CH3 NH2 CH3 ][Tb(ox)2 (H2 O)]· 3H2 O (Tb-MOF). It shows a 3D anionic framework, which featured one-dimensional (1D) channels (about 13.06 × 13.06 Å 2 ) along the a-, b-, and c-axes, which resulted in a high surface area, as measured by Brunauer–Emmett–Teller (BET) surface area, of 37.585 m 2 /g. The N2 /CO2 adsorption for the complex was measured at 77 K. The solid-state Tb-MOF exhibited strong green luminescence assigned to the 5 D4 → 7 FJ (J = 6–3) transition in the visible region, which can be observed by the naked eye under irradiation with 365 nm near-UV light. When immersing Tb-MOF in aqueous solutions, the Tb(III) characteristic luminescence was also maintained and its emission with maximum intensity was reached over the pH range 4–11. The complex was an attractive luminescence material, and its luminescence sensing properties were discussed in detail. Fluorescent measurement results show that the complex had high sensitivity detection for imidacloprid and thiamethoxam in water solutions with low detection limits of 1.3 × 10 −5 M −1 and 7.3 × 10 −6 M −1, respectively. Also, Tb-MOF has been explored for the adsorption and release of ibuprofen. Graphical abstract: A new synthesized Tb-MOF is a 3D microporous framework with a high surface area. The adsorption properties of the Tb-MOF have been studied and the complex have high sensitivity detection for imidacloprid and thiamethoxam in water solutions. Image 1 Highlights: A 3D anion framework with one-dimensional (1D) channels along the a-, b-, and c-axes was synthesized. Tb-MOF has a high surface area, as measured by Brunel-Emmett-Teller (BET) surface area, 37.585 m 2 /g. Tb-MOF can selectively detect imidacloprid and thiamethoxam in aqueous solutions with high sensitivity.